PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Arif Fajrianto; Surya Raharja (Diponegoro Journal of Accounting, 2021)
The aim of this study is to examine the role of corporate governance iniintellectual capital disclosure. This study uses firm size, leverage and return on asset as a control variable. The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2016 - 2018. Sample determined with purposive sampling method. Total sample of this research are 327 companies. This study used multiple regression analysis for hypotheses testing. The results of this study show that board size and government ownership has positive and significant effect on intellectual capital disclosure. Meanwhile, the proportion of independence, blockholder ownership, board tenure has no effect on intellectual capital disclosure.